TEMPORAL POLITICS IN THE BPO INDUSTRY: DISCIPLINE, VULNERABILITY AND NEGOTIATION OF YOUNG WORKERS IN YOGYAKARTA: Politik Waktu dalam Industri BPO: Disiplin, Kerentanan, dan Negosiasi Pekerja Muda di Yogyakarta - Michael A.S. Dharmaputra (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
The Business Process Outsourcing (BPO) industry in Indonesia has expanded rapidly alongside the growth of digital companies that rely on standardized and time-based services. In Yogyakarta, this expansion is supported by the availability of young workers and relatively low regional minimum wages, which create flexible yet tightly controlled work environment. This study aims to examine how BPO workers experience time in their daily work and how they negotiate its pressures within digitally managed labor systems. Using a corporate ethnography approach, the research was conducted over five months through participant observation and in-depth interview with nine workers from three BPO companies in Yogyakarta.The findings show that algorithmic management, short-terms contracts, and real-time performance monitoring produce strict temporal discipline that reshape workers daily rhythms and limit control over their own time. Under these conditions, workers develop tactical strategies such as regulating response timing, delaying new interactions, and planning absences in order to cope with pressure and maintain emotional stability. However, these strategies only create limited spaces for negotiation within a broader structure of digital capitalism that perpetuates job insecurity and precarity. This study contributes to the anthropology of work by highlighting how time operates as a mechanism of power in the BPO industry and enriching critical discussions on digital labour in Indonesia.